The understanding of refers and trainers of basketball game rules - Oki Candra; Dupri; Tri Prasetyo (UIR Press, 2021)
The background of this research is that there are still some basketball referees and coaches whose level of understanding is still lacking in the rules of the basketball game, seen during the game process, there are often debates between coaches and referees. The purpose of this study was to see the differences in the understanding of referees and basketball coaches throughout Riau on the rules in basketball games. This type of research is a comparative descriptive research, namely research that compares two different variables. The method used in this study is a survey method and data collection techniques using true-false tests. The population in this study were referees and coaches throughout Riau. The research sample was taken using a random sampling technique, totaling 25 trainers and 16 referees who were active throughout Riau Province. The results of this study obtained a sig value of 0.141 (p>0.05). So it can be concluded if there is no difference in the understanding of the referees and basketball coaches in Riau on basketball rules. If in hypothesis 1 it is said that there is no difference in understanding because the sig results obtained are p> 0.05. This happened because the average understanding of the coach and referee were both in the medium category. Research contributes to education, especially in the basketball branch, where this research can be known and understood by referees and coaches, so that in a basketball game a conducive game will be created.